APPLICATION OF ARTIFICIAL INTELLIGENCE IN ENSURING PUBLIC SAFETY (EXPERIENCE OF FOREIGN COUNTRIES) - I. I. Murakayev (Journal Park Publishing, 2025)
Modern artificial intelligence technologies (hereinafter referred to as AI) are actively being introduced into various spheres of life, including public safety. This article explores key AI-based solutions implemented in foreign countries to enhance the effectiveness of security systems. It also analyzes current trends and prospects for the use of AI in law enforcement, transportation, emergency management, and counter-terrorism.
Keywords: Artificial intelligence, AI solutions, public safety, public security system, predictive analytics, Big Data, software, automation, ethics.